Immigration, Generation and Self-rated Health in Canada: On the Role of Health Literacy - Omariba, D. Walter Rasugu (Can J Public Health, 2011)
OBJECTIVES: The purpose of this study was to determine whether there are differences in self-rated health by immigration and generational status, and the role of health literacy in this relationship. METHODS: Data were from the Canadian component of the 2003 International Adult Literacy and Skills Survey (IALSS) undertaken by Statistics Canada. The sample comprised a total of 22,818 persons, of whom 3,861 were immigrants and 18,957 non-immigrants. The study employed logistic regression to examine the relationship between health literacy and self-rated health. The analysis separately compared: immigrants and non-immigrants; immigrant groups defined by region of origin and recency of arrival in Canada; and the local-born defined by generation. RESULTS: Logistic regression results indicated that immigrants compared to non-immigrants, and recent immigrants not from Europe or USA compared to established immigrants from Europe or USA, were more likely to report good self-rated health. On the other hand, compared to the third-plus generation, the second generation were less likely to report good self-rated health. Health literacy was positively associated with good self-rated health. However, its effect was largely accounted for by discordance between mother tongue and language of survey administration among immigrants, and by literacy practices at home, education, place of residence, and income among non-immigrants. CONCLUSION: Health literacy is important in the health of both immigrants and non-immigrants, but with different underlying mechanisms. For nonimmigrants, engaging in literacy practices at home would benefit both health literacy and overall health, whereas for immigrants, it would be improving proficiency in either English or French.